Implementación de un sistema de gestión de historias Odontológicas y Odontograma digital mediante el uso del framework .net y api_rest para el consultorio “Salud Dental” del sector Guaytacama - Bermeo Alvarado, Renato Joel (2022)
This research work was developed in the "SALUD DENTAL" dental office located in the parish of Guaytacama, which was based on the implementation of a computer system for the management of dental records and the management of a digital odontogram for the dental treatment of patients. Thus, it was necessary to investigate and study the current operation of this area and thus to point out the problems that were presented in terms of the processes that are performed in the dental office, for this, an interview was conducted to obtain the requirements of the system based on these problems and thus design an effective architecture that manages to meet all the requirements established. The development of the system was based on the Scrum methodology jointly adapting all the tools that this methodology offers us to obtain an optimal development of the system, using software tools such as C# using the .NET framework, as well as the use of apis_web through the ASP.NET framework, and SQL SERVER as database manager. It could be concluded that with the development of the system benefits will be obtained, such as a great reduction of time in their services, the danger of loss in terms of patient information, as well as their medical records and management in the processes that are carried at the time of dental treatments. With the results obtained, the project provided a great technological benefit to both the workers of the dental office and their patients.